2016
DOI: 10.1016/s2468-1253(16)30082-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular fluorescence-guided surgery of peritoneal carcinomatosis of colorectal origin: a single-centre feasibility study

Abstract: FP-7 Framework Programme BetaCure and SurgVision BV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
120
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(132 citation statements)
references
References 16 publications
(29 reference statements)
2
120
0
4
Order By: Relevance
“…Targeted NIR fluorescence imaging has already been studied in several clinical trials for colorectal, head and neck, pancreatic and renal cancer and has shown its potential and added value in intraoperative decision making 21,25,[31][32][33] . As a result of these trials, a variety of suitable biomarkers have been identified for NIR-fluorescence guided surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted NIR fluorescence imaging has already been studied in several clinical trials for colorectal, head and neck, pancreatic and renal cancer and has shown its potential and added value in intraoperative decision making 21,25,[31][32][33] . As a result of these trials, a variety of suitable biomarkers have been identified for NIR-fluorescence guided surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence imaging (FI) is ideal for intraoperative applications due to fast acquisition times (milliseconds), flexibility in application, and portability [2]. Various tumor-targeted near-infrared (NIR) fluorescence agents have been successfully studied in clinical trials [3][4][5][6]. Moreover, there is great potential for a broad range of clinical applications besides oncology, such as infectious and inflammatory diseases [7].…”
Section: Introductionmentioning
confidence: 99%
“…Comparable targeted fluorescent techniques have been established in other tumour types, e.g. in ovarian carcinoma [17, 53] and peritoneal metastases of colorectal carcinomas [18] targeting αvβ3-integrin or folate receptor α and VEGF-α, respectively. For the development of a similar approach in meningioma surgery, various biomarkers have been suggested, including epithelial membrane antigen (EMA), platelet-derived growth factor beta (PDGF-β), vascular endothelial growth factor A (VEGF-α), and somatostatin receptor type 2 (SSTR-2) [3, 5, 9, 11, 12, 16, 19, 21, 28, 30, 32, 38, 39, 43–45, 48, 52, 56].…”
Section: Introductionmentioning
confidence: 99%